The role of language on assessment outcomes: an analysis of questions in English classrooms - Turayeva Umida (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA'LIMNING INNOVATSION YO'NALISHLARI, 2024)
The following paper researches that the general practices associated with formative assessment can simplify learning, prevailing definitions acknowledge such a vast variety of operations that effects should be anticipated to vary widely from one implementation and student population to the next. In addition, the extent of commonly made quantitative claims for effectiveness is suspect, deriving from imperceptible, imperfect, old, or unpublished sources. To comprehend extreme advantage from formative assessment, new development should focus on conceptualizing well‐specified approaches built around process and methodology engrained within specific content domains. Those conceptualizations should incorporate fundamental quantity values that encourage teachers and students to distinguish the inferential nature of assessment.